Production and Profitability of Honey in Yewa North, Nigeria - Abere, S.A.; Lameed, G. A. (Mediterranean Journal of Social Sciences, 2012)
The study examined the level of production, supply and marketing of honey in Yewa North LocalGovernment Area of Ogun State. Some hindrance to honey supply and marketing were also identified. Toachieve the aim of this study, fifty (50) questionnaires were distributed to five communities randomlyselected in the study area. Ten questionnaires were administered in each community to collect data frombeekeepers. The socio economic variables analysis revealed that 64% of the apiculturists were males while36% were females. Up to 62% of the apiculturists were Christians while 36% were Muslims and 2% of themwere neither Christians nor Muslims. Majority of the producers were in the range of 30-40 years. 4% of thehoney producers were singles while 96% were married. NCE holders were 30% while 10% were degreeholders. Fifty two percent of the apiculturists inherited the farmland while 9% purchased land. Top barshive were used by 84%, while 6% used langsroth and 10% used other type of hives. Traditional method ofbeekeeping was used by 14%, while 86% used modern method of beekeeping. This study shows that 20%of the apiculturists chose beekeeping as their main occupation while 80% chose apiculture as secondaryoccupation. Only the sales of honey were used for the budgetary analysis. The cost analysis shows that thecost of hive which was 44.5% constitutes a large percentage of the total cost of honey production. The fixedcost was 91.5% of the total cost while the variable cost was 8.4% of the total cost of honey production inthe study area.The profitability index was 0.6058 which implies that for every N1 sales, 60k was earnedwhile the rate of return on investment and variable cost are 153.7286 and 1921.3. The gross margin andthe net farm income are 300687.0 and 188567.4. The operating ratio is 0.0332 which means that the totalvariable cost is about 3.3% of the total revenue while the benefit cost ratio is 2.5651 which imply that therisk of running at a loss if invested in the enterprise is very minimal and the probability of making profit ishigh.